A educação profissional e tecnológica no contexto da expansão dos institutos de educação, ciência e tecnologia (lei 11.892/08) - Mello, Cleverson Molinari (2017)
The objective of this study is to analyze the interests that guided the creation and expansion of the Institutes of Education, Science and Technology through Law n. 11.892 / 08 contained in a government policy (begun in 2003) in its proposal of Professional Education. The hypothesis raised that the said expansion is guided by recommendations of international organs and neoliberal policies has among its fundamental scopes the following aspects: Better qualification of the worker, aiming to meet the interests of Capital, by increasing productivity and competitiveness of companies, through greater exploitation of the workforce; Get support from the mass of workers, future workers and society in general, evoking education as a strategy for social cohesion, repeating the mystification of education as a means of social mobility; The maintenance and extension of courses of short duration and more flexible submissive to the logic of the market and therefore, disposable, create a false illusion of employability in the worker. The dependence of these courses on the variations of industry, the market and new technologies and work processes subject the worker to a state of uncertainty and precariousness. Therefore, the changes through which Brazilian education has passed and is passing, in particular, professional education, portrays the political battle on the part of the ruling class that, therefore, conflicts with the interests of the working class. The model of professional education that has been adopted in Brazil, shows the characteristic of the State, that is, of submission to market agents. In view of the analyzes carried out in the present study and the confirmed hypotheses, it was possible to better understand the interests that guided the creation and expansion of the Federal Institutes, who is interested in this expansion and what is behind the documents analyzed. If, on the one hand, the expansion of the Federal Network of Professional and Technological Education expresses a government policy guided by recommendations of international and neoliberal policies, on the other hand, the creation of the Federal Institutes throughout Brazil, even in the most distant places of the country, is considerable and gives the worker the possibility of professional qualification.